PENGARUH KERJA TIM TERHADAP KEPUASAN KERJA MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI di AJB BUMIPUTERA 1912 CABANG DARMO SATELIT SURABAYA - ALI WAFA, MUHAMMAD (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract One of the companies national insurance that will bring a kind of life insurance is AJB Bumiputera 1912 the branch Darmo Satellite Surabaya. This research on the ground by phenomena gap and research gap, In the company AJB Bumiputera 1912 Darmo Satelit Surabaya branch provides reward incentives in the form of vacation abroad, monthly bonus, family gathering held at the end of first quarter, end of second quarter, and promotion of position from staff to middle class manager, punishment. To know the progress of employee performance. Then the presence of employees who do not enter without notice to make his work increasingly piled up. The purpose of this research is to analyze and discuss the influence of team work against satisfaction working through that organization commitment as variable mediation. Respondents in this research was all of the employee AJB Bumiputera 1912 the branch of Satellite Darmo Surabaya. A method of the determination of the sample is using the sampling method of saturated. Sample in use as many as 32 people. Data collection techniques in use in this research was of the questionnaire was. Data analysis technique using analysis through mediation with the program smart pls version 2.0. Keywords: working team, job satisfaction, organization commitment